About the lives and times of extraordinary entrepreneurs: The methodological contribution of autobiographies to the life course theory of entrepreneurship. (3rd September 2021) - Hulsink, Willem; Rauch, Andreas
ABSTRACT: There have been recent calls in the entrepreneurship literature to shift research paradigms toward more relevant, contextual, and process-oriented research. We respond by proposing a life course perspective on firms and their creators using alternative sources of information, specifically life history data included in autobiographies written by the founders of well-known firms. Autobiographies as self-narratives describing how the founders and their firms evolved and any dramatic events that interrupted that process provide unique insights not obtainable from other research materials. This paper introduces retrospective analysis of the life course of entrepreneurs and the evolution of their firms, including critical stages and transitions, and reflection on what was achieved and what was not. To guide researchers, we provide an overview of methodologies used to analyze autobiographies, discuss their strengths and limitations, and suggest potential research designs.